1970
DOI: 10.1017/s0021859600026009
|View full text |Cite
|
Sign up to set email alerts
|

The nutrition of the early weaned lamb:II. The effect of dietary protein concentration, feeding level and sex on body composition at two live weights

Abstract: 1. In an experiment with ninety-nine lambs the effects on the body composition of male and female lambs were examined when five diets containing different concentrations of crude protein (in the range 10-20 %) were given at three levels of feeding and lambs were slaughtered at two live weights (27-5 and 40 kg).2. With lambs slaughtered at 27-5 kg there were significant increases in the rate of both nitrogen and fat retention with increases in levels of feeding. There were also linear increases in the rate of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
28
0

Year Published

1980
1980
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(33 citation statements)
references
References 11 publications
5
28
0
Order By: Relevance
“…Similarly, Silva et al (2001) verified that Santa Ines lambs were more demanding for net protein for gain when compared to Ideal and Ile de France lambs, and protein requirement values were about 20% higher than those adopted by ARC (1980) for lambs with body weight between 20 and 30 kg. Andrews & Orskov (1970), testing diets containing cereals ranging in protein concentration from 10 to 20% for Suffolk crosses weighing 20 kg, verified a quadratic response for weight gain, and no weight gain increases were obtained consistently with the increase in protein content above 17.5%. On the other hand, Manso et al (1998a), evaluating three protein sources with levels of 16.5; 22 and 23.7% CP in diet dry matter (DM) for Merino lambs, observed that diets of higher CP contents were better taken in, presented higher average daily gain and better feed conversion.…”
Section: Introductionmentioning
confidence: 79%
“…Similarly, Silva et al (2001) verified that Santa Ines lambs were more demanding for net protein for gain when compared to Ideal and Ile de France lambs, and protein requirement values were about 20% higher than those adopted by ARC (1980) for lambs with body weight between 20 and 30 kg. Andrews & Orskov (1970), testing diets containing cereals ranging in protein concentration from 10 to 20% for Suffolk crosses weighing 20 kg, verified a quadratic response for weight gain, and no weight gain increases were obtained consistently with the increase in protein content above 17.5%. On the other hand, Manso et al (1998a), evaluating three protein sources with levels of 16.5; 22 and 23.7% CP in diet dry matter (DM) for Merino lambs, observed that diets of higher CP contents were better taken in, presented higher average daily gain and better feed conversion.…”
Section: Introductionmentioning
confidence: 79%
“…Thus, energy supplementation at low levels of dietary protein might not necessarily be associated with significant increases in energy supply to the animals. Andrews and Ørskov (1970), using early-weaned lambs fed with diets containing increasing concentrations of protein at low, medium, or high levels of feeding, observed that, when feed intake limited N retention, the lambs did not significantly increase protein deposition in response to increasing amounts of protein supplementation, suggesting the existence of an energy-dependent phase of growth. On the other hand, at the highest level of feeding, there was a linear increase in N retention as protein intake increased, until reaching a point where energy (or another factor) became most limiting, at which point no further responses to protein intake were observed.…”
Section: Variation In Nutrient Intakementioning
confidence: 99%
“…If that is not considered, erroneous interpretations can be made. For example, re-analyzed the data of Andrews and Ørskov (1970), considering the finding of the complementary study of Ørskov and Fraser (1973). By estimating total N supply in the small intestine for the dietary treatments used by Andrews and Ørskov (1970), it was observed that increasing the feeding level to increase energy intake was also associated with greater amounts of both microbial and dietary N arriving to the small intestine (Ørskov and Fraser, 1973).…”
Section: Variation In Nutrient Intakementioning
confidence: 99%
See 1 more Smart Citation
“…). In another connection, compensatory growth adjustments take place when lambs are able to govern their own apetite (Andrews and 0rskov, 1970;Ferrell et al, 1986;Turgeon et al, 1986). The regularity of the growth curve consequently depends on growth rate in the post-weaning stage as lambs enter the feed-lot.…”
Section: Introductionmentioning
confidence: 99%